Analysis of the Causes of Defects in the Timber Production Process Using the FMEA (Failure Mode Effect Analysis) Method Approach at PT. KQW - Prasmana, Muhammad Farid; Andesta, Deny; Hidayat, Hidayat (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
PT. KQW is related to quality. Some problems occur during the production process and product results, which are associated with the level of defects in the production process. From historical production data for April 2022 – June 2022, glulam wood products contribute the most defects, both congenital physical defects of the material itself and during the production process. This study aims to identify the level of defects in wood products, determine the factors that cause defects in wood products, and determine the efforts made to reduce the level of damage to wood products. The formulation of the problem in this study is how to control the damage/defects of wood products faced by PT. KQW. This research method uses FMEA. This research resulted in defects in the production process of glulam wood cracks, holes and breaks. The highest types of defect are hollow wood. Identification of the causes of every kind of defect, the order of the highest RPN value for each NG defect. There are 3 solution recommendations based on the highest RPN value for each defect. For cracked wood defects, the highest RPN is because the workers are less thorough (100). Then for hollow wood defects, the highest RPN is due to poor raw materials (147). The highest RPN for broken wood defects is due to less engine pressure (224).                                                                                                                          Keywords:FMEA, Timber Production Process, RPN, Defect, Failure